1999
DOI: 10.1021/ma981190p
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Biodegradable Thermosensitive Polymers. I. Synthesis and Characterization of Poly(organophosphazenes) with Methoxy-Poly(ethylene glycol) and Amino Acid Esters as Side Groups

Abstract: Novel thermosensitive poly(organophosphazenes) bearing methoxy-poly(ethylene glycol) (MPEG) and amino acid esters as substituents have been synthesized, and their lower critical solution temperature (LCST) was investigated. Differential scanning calorimetry (DSC) has shown that some of the polymers exhibit crystallinity, which is probably induced by the MPEG side chain of the polymers. Most of the polymers show their LCSTs in the range of 25.0−98.5 °C, depending on several factors such as mole ratio of the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 18 publications
5
101
0
1
Order By: Relevance
“…Many homo-and copolymers of NiPAAm are not biodegradable [48], a fact that may prove problematic for some biomedical engineering applications. Nakayama and colleagues [37] have prepared thermally responsive, biodegradable polymeric micelles for controlled drug release.…”
Section: N-isopropylacrylamide-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many homo-and copolymers of NiPAAm are not biodegradable [48], a fact that may prove problematic for some biomedical engineering applications. Nakayama and colleagues [37] have prepared thermally responsive, biodegradable polymeric micelles for controlled drug release.…”
Section: N-isopropylacrylamide-based Systemsmentioning
confidence: 99%
“…Poly(organophosphazenes) grafted with mPEG and amino acid esters were reported as a new class of biodegradable and thermosensitive polymers in 1999 [48]. Sohn and colleagues [80] developed a correlation for the LCST of these polymers as a function of their molecular structure, which comprises hydrophilic (PEG) and hydrophobic (amino acid esters) side groups.…”
Section: Poly(organophosphazenes)mentioning
confidence: 99%
“…Among the poly(organophosphazenes) with methoxy-poly(ethylene glycol) and amino acid esters as side groups previously synthesized, 14 Measurements of LCST. The LCST temperature of the aqueous solution of the polymer (5%) containing different kinds and concentrations of saccharides (0-1.0 M) was detected visually in a closed glass tube and the temperature was controlled by immersion of the glass tube in an oil bath.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 In our previous work, it was reported that the poly(organophosphazenes) bearing methoxy-poly(ethylene glycol) (MPEG) and amino acid esters as side groups are not only biodegradable but also thermosensitive, showing a wide range of LCST depending on compositions and kinds of the side groups. 14 We have also studied the salt effect on these polymers in aqueous solutions. 15 In this study, saccharide effects on the LCST of poly-(organophosphazenes) were investigated in detail employing several structurally different saccharides.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the temperature sensitivity of swelling can be attributed to the delicate hydrophilic-lipophilic balance (HLB) of polymer chains and is affected by the size, configuration, and mobility of alkyl side groups. A sharp swelling transition occurs at LCST, when an optimum HLB value is attained in networks demonstrating sharp thermoresponsive properties; such as poly(NIPAM) networks [161,162].…”
Section: Temperature-sensitive or Thermo-responsive Gelsmentioning
confidence: 99%